2018
DOI: 10.1101/311258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Home ground advantage: selection against dispersers promotes local adaptation in wild Atlantic salmon

Abstract: A long-held, but poorly tested, assumption in natural populations is that individuals that disperse into new areas for reproduction are at a disadvantage compared to individuals that reproduce in their natal habitat, underpinning the eco-evolutionary processes of local adaptation and ecological speciation. Here, we capitalize on fine-scale population structure and natural dispersal events to compare the reproductive success of local and dispersing individuals captured on the same spawning ground in four consec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…To increase our confidence in inferred male genotypes, we used a previous estimate of genotyping error of 0.14% for the microsatellite panel developed by Bradbury et al (2018) to provide as input in Colony2. Mobley et al (2018) showed that local Atlantic salmon exhibit higher fitness in their native river compared with dispersers straying from other populations. Therefore, we conducted a firstgeneration (F 0 ) migrant detection analysis with Geneclass2 (Piry et al, 2004) to remove those potential dispersers from statistical analysis pertaining to the comparison of reproductive success between wild and captive-bred salmon.…”
Section: Parental Allocation Of Frymentioning
confidence: 99%
“…To increase our confidence in inferred male genotypes, we used a previous estimate of genotyping error of 0.14% for the microsatellite panel developed by Bradbury et al (2018) to provide as input in Colony2. Mobley et al (2018) showed that local Atlantic salmon exhibit higher fitness in their native river compared with dispersers straying from other populations. Therefore, we conducted a firstgeneration (F 0 ) migrant detection analysis with Geneclass2 (Piry et al, 2004) to remove those potential dispersers from statistical analysis pertaining to the comparison of reproductive success between wild and captive-bred salmon.…”
Section: Parental Allocation Of Frymentioning
confidence: 99%
“…Another explanation for the lack of selection in males could simply be that there is little variation in male size in this population, and hence a reduced scope for selection. For example, Atlantic salmon in the River Teno/Tana in Finland/Norway exhibit a much larger range of male body sizes, and selection for larger males is known to occur there (Mobley et al, 2019; see also Fleming, 1998). Anthropogenic changes over the past several decades, particularly in the marine environment, have reduced the prevalence of larger, older salmon in some populations across their range (Chaput, 2012;Quinn et al, 2006;Reed et al, 2017), including the Burrishoole (Nixon, 1999), which may in turn limit the opportunity for ongoing selection.…”
Section: Selection Analysesmentioning
confidence: 99%
“…Within-river structuring is also believed to reflect local adaptation because even weak genetic structure within river systems can correspond to biologically meaningful differences in growth and survival among populations (e.g. Aykanat et al, 2015;Mobley et al, 2018). Despite the belief that Atlantic salmon exhibit widespread local adaptation, the genomic basis of many adaptive traits remains unclear.…”
Section: Introductionmentioning
confidence: 99%